2016
DOI: 10.1080/13825585.2016.1268674
|View full text |Cite
|
Sign up to set email alerts
|

Intraindividual reaction time variability predicts prospective memory failures in older adults

Abstract: Article:Haynes, BI orcid.org/0000-0003-0054-6591, Kliegel, M, Zimprich, D et al. (1 more author) (2018) Intraindividual reaction time variability predicts prospective memory failures in older adults. Aging, Neuropsychology, and Cognition, 25 (1 ReuseUnless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
12
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 37 publications
4
12
1
1
Order By: Relevance
“…A promising method for studying the relationships of MVPA and CRF to cognitive function is to use a measure of intraindividual variability (IIV) of response time (RT), which has been validated as an important metric of executive function 22 . Specifically, IIV in performance can be measured by examining trial-by-trial fluctuations in RT and reflects dynamic variability in attentional or executive control 23 . A growing body of evidence in older adults suggests that it is an important index of information processing efficiency, 24 a sensitive indicator of neurobiological integrity, 22 and a potential predictor of memory failures, 23 dementia, 25 and mortality 26 …”
Section: Introductionmentioning
confidence: 99%
“…A promising method for studying the relationships of MVPA and CRF to cognitive function is to use a measure of intraindividual variability (IIV) of response time (RT), which has been validated as an important metric of executive function 22 . Specifically, IIV in performance can be measured by examining trial-by-trial fluctuations in RT and reflects dynamic variability in attentional or executive control 23 . A growing body of evidence in older adults suggests that it is an important index of information processing efficiency, 24 a sensitive indicator of neurobiological integrity, 22 and a potential predictor of memory failures, 23 dementia, 25 and mortality 26 …”
Section: Introductionmentioning
confidence: 99%
“…Loft and co-workers thus suggested that increased mean RT and variability reflect regular monitoring for the prospective target. In contrast, Haynes et al consistently found increased IIV in independent working memory and processing speed tasks to be predictive of lower performance on a composite PM score [63]. These authors speculated that the shared association between IIV and PM performance may arise from fluctuations in focus on the task and target monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, more recent work has also highlighted age-related increases in intra-individual variability on a number of these tasks [108-110]. Far from being epiphenomenal, changes in intra-individual variability may both precede and predict future cognitive declines, suggesting that this measure may represent an important predictive tool in the etiology of pathological aging [111-113]. It is currently unknown if intra-individual variability is domain general and observed across a wide range of sensory processing, or if it is more specific to certain kinds of sensory and multisensory processes.…”
Section: Introductionmentioning
confidence: 99%